Cultural icons of the Philippines - Dela Torre, Visitacion R. (Makati City Tower Book House, 2002)
This book, Cultural icons of the Philippines, is all about cultural icons that represent the country and as well as the Filipinos. Examples of which are Banaue Rice Terraces; jeepney, sungka, nipa hut; Dr. Jose Rizal; vinta; mango; balut; Nora Aunor, Dolphy; Boracay; sinigang; Manila Bay sunset; halo-halo and many more. In this book, Chit dela Torre discusses the social life and customs of the Filipinos. She also describes the national characteristics of the Filipinos and how it shaped them to be what they are today. For purposes of practical classification, the book is divided into several categories: a) material objects from nature b) food and beverage/drinks c) tourists destinations d) cultural practices or traditions and e) personalities from heroes to cultural divas to sports and pop icons. The last chapter of the book features prominent Filipinos who express their own choices of cultural icons and why. The images in the book are colored and its intended audience is for everyone.
Keywords: National characteristics, Filipino; Philippines -- Social life and customs; Philippines -- Civilization; Philippines -- Biography